Understanding the relationship between synthetic conditions, porosity and CO2 uptake capacity of turbostratic carbons - Blankenship, L. Scott (2023)
As of 2021, the atmospheric concentration of CO2 is 412 ppm and continues to rise. It is well established that these concentrations are resulting in rising temperatures, an increased incidence of extreme weather, and thus unspeakably disastrous consequences for all life. It follows then that CO2 capture and removal technologies must be rapidly developed to ensure the longevity of human society. One area of research is CO2 capture via physisorption onto porous materials and in particular on the easily synthesised turbostratic carbon. This application requires fine control over porosity (surface area, pore volume, pore size) according to conditions of sorption, and it therefore follows that both the ability to precisely measure pore sizes, as well as a definitive knowledge of the relationship between CO2 uptake capacity and pore size is needed. This thesis attempts to address all three of these issues.